2021
DOI: 10.1177/17151635211014918
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-led sedative-hypnotic deprescribing in team-based primary care practice

Abstract: Background: Sedative-hypnotic (SH) medications are often used to treat chronic insomnia, with potentially serious long-term side effects. The objective of this study is to evaluate an interprofessional SH deprescribing program within a community team-based, primary care practice, with or without cognitive behavioural therapy for insomnia (CBT-I). Methods: Retrospective chart review for patients referred to the team pharmacist for SH deprescribing from February 2016 to June 2019. Results: A total of 121 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The collaboration resulted in a significant reduction in the number of PIMs immediately and at 12-month follow up compared to the control group. Our results also underscore the benefits of engaging specialized health care professionals, including the expertise of geriatricians and clinical pharmacists, to lead and sustain deprescribing efforts in the busy primary care setting to improve patient outcomes ( Lui et al, 2021 , Wong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 61%
“…The collaboration resulted in a significant reduction in the number of PIMs immediately and at 12-month follow up compared to the control group. Our results also underscore the benefits of engaging specialized health care professionals, including the expertise of geriatricians and clinical pharmacists, to lead and sustain deprescribing efforts in the busy primary care setting to improve patient outcomes ( Lui et al, 2021 , Wong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 61%
“…The twenty studies included in the review were conducted in different health settings: hospitals ( n = 8), 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 community pharmacies ( n = 4), 25 , 45 , 46 , 47 and primary care centres ( n = 2). 24 , 48 Other settings include intermediary care, such as subacute medical outpatient clinics, 22 residential care settings, 23 , 49 long-term care, 50 nursing facilities, 51 and geriatric oncology clinics at cancer centres. 52 Most of the studies were conducted in high-income countries, including Canada ( n = 7), 38 , 43 , 45 , 46 , 47 , 48 , 50 United States of America ( n = 4) (USA), 24 , 37 , 39 , 52 Australia ( n = 3), 41 , 44 , 49 Denmark ( n = 2), 22 , 40 and Netherlands (n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…This evaluation is one of the few studies that evaluate a combined patient‐ and clinician‐outreach method aimed at benzodiazepine deprescribing in a primary care setting. Previous US and Canadian studies of pharmacist‐led benzodiazepine tapering have focused on both younger and older adult populations referred by clinicians, rather than through direct patient outreach, and found comparatively higher benzodiazepine discontinuation rates 15,16 . Additionally, the EMPOWER trial, a Canadian cluster randomized trial which examined direct patient outreach via an educational brochure in outpatient pharmacy settings found that 67% of participants discussed deprescribing with their physicians and 27% completely or partially tapered benzodiazepines 17 .…”
Section: Discussionmentioning
confidence: 99%